A five-year strategic Financial Plan for Raslag Corp. - Boqueo, Jj B., Castillo, Czaren M., Cardeña, Bernadette V., Costoy, Ma. Justine F., Felix, Maxine C., Galosa, Ma. Sofia Justlyn B., Gonzales, Jascha Rae P., Legaspi, Shannen Trishia S., Omega, Angelo S., Santiano, Aira Mae G. 4 0 16; 5
Abstract This paper provides an in-depth study of RASLAG Corp., a visionary provider of renewable energy based in Kapampangan that specializes in solar energy. Since its establishment in 2013, RASLAG has quickly gained notoriety, employing 27 people to run five ground-mounted solar power plants in Mexico and Magalang, Pampanga. Despite these, the business still faces difficulties that are common to a developing sector. Through this study, we sought to identify these issues which turned out to be their profitability ratios, and thus, provide a strategic solution-to invest in a Smart Cloud Software system in order to improve management and profitability over time and streamline processes. RASLAG wants to overcome challenges, increase profitability, and penetrate new markets in the Philippines by utilizing technology.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2